The marks of madness in prison: a reading of the archive of the Museum of Flags (Goiás city, Brazil) (Cadernos de Sociomuseologia, 2025)
The purpose of this article is to analyze the marks left in the building of the former House of Chamber and Jail, current Museum of Flags (MuBan), probably by the individuals imprisoned there, from the archive of the institution, which holds these voices that need to be, more than heard, problematized in exhibitions. Among the various possible memories that the history of the MuBan building contains, from 1766, when it was built, until 1949, when it ceased to be a jail, we will prioritize the insane, or individuals classified as such. These stories need to get out of these shadow zones of the past; However, it is a living past, since it is embedded not only in the walls, but in the whole building. For this, we divide the article into two parts, in the first we analyze the museums as a space of madness memory, and in the second, we will deepen in the marks of madness from the MuBan archive. The main objective lies in the possibility of problematizing these issues aiming at the creation of future exhibitions.Keywords: Museum; Madness; Archive; Goiás City.